A Pilot Study of a Picture- and Audio-assisted Self-interviewing Method (PIASI) for the Study of Sensitive Questions on HIV in the Field. Issue 1 (February 2016) - Aarnio, Pauliina; Kulmala, Teija
Self-interview methods such as audio computer-assisted self-interviewing (ACASI) are used to improve the accuracy of interview data on sensitive topics in large trials. Small field studies on sensitive topics would benefit from methodological alternatives. In a study on male involvement in antenatal HIV testing in a largely illiterate population in Malawi, we piloted picture- and audio-assisted self-interviewing (PIASI). Out of 388 participants, 96 were randomized to answer six sensitive questions using PIASI after the face-to-face interview (FTF). Participants who responded by PIASI were more likely to express accepting attitudes toward childbearing by HIV-positive women than were FTF respondents. Most considered PIASI easy to use, and one in five preferred it to FTF. PIASI may offer a feasible, low-cost alternative to ACASI for small and simple studies on sensitive topics and in illiterate populations.